The FT-IR spectroscopic investigation of transition metal(II) 4-aminopyridine tetracyanonickelate complexes - AKYÜZ, SEVİM (Elsevier, 1999)
FT-IR spectra of M(4Apy)2Ni(CN)4 {where M=Mn, Co, Ni, Cu or Cd; 4Apy=4-aminopyridine} complexes are reported for the first time in the 400–4000 cm−1 range. The spectral features suggest that the compounds are similar in structure to the Hofmann-type complexes with infinite polymeric layers formed with Ni(CN)4−2 ions bridged by M(4Apy)2+2 cations and the ring nitrogen of the 4Apy is only involved in complex formation. However in some cases host complexes include H2O molecules as guest species which are found to be H-bonded to hydrogens of the amino group of 4Apy (N–H⋯OH2). The coordination effect on the 4Apy modes is analysed.
Keywords: FT-IR; Aminopyridine; Hofmann type complexes; Tetracyanonickelate; Transition metal